O paradigma emergente e a abordagem do ensino com pesquisa uma proposta de resignificação para o ensino de Biblioteconomia e Ciência da Informação no Brasil: uma proposta de resignificação para o ensino de Biblioteconomia e Ciência da Informação no Brasil - Mara Eliane Fonseca Rodrigues (2008)
It relies on the foundation of the emerging paradigm to rethink pedagogical practices adopted by Library Science and Information Science professors, trying to establish the grounds for the constructions of new didactics for the area, based on teaching and research. It believes that research, as instrument for teaching and as learning content, may show that there is another way to conceive knowledge: not as something static and linear, but interlaced with different approaches of knowledge; that is, process and product at the same time. It may also discuss the teaching techniques of each professor involved in the educational/formational process of science information professionals, in terms of undergraduate courses, throwing some light on new paths for the formation of those professionals. Therefore, at first, it helps professors to think about science paradigms and their influence on pedagogical approaches that orient the teaching/learning process for the area. Afterwards, it shows general ideas that oriented science for a long time and briefly describes the history of modern science and the consequences of this triumph in Education. Then, it analyses the strong influence of Cartesian-Newtonian thinking about Education, emphasizing its limitations in terms of world vision and value system. Right after, it shows a thorough exam of an emerging way of thinking the world and its impact on education. Continuing, it strives to locate Library Science and Information Science in this transitional context, acknowledging its interdisciplinary relationships and their influence in the formation process of Brazilian professionals. Due to theoretical as well as practical changes in professional formation, it shows the necessity of greater interaction with the educational field. Also, it presents a pedagogical practice for Library Science and Information Science based on the paradigmatic changes of science, mainly the teaching and research approaches. Next, it explains the methodological procedures used to develop research in its different moments. Later, based on the principle that it is with the orientation of the professor that the students effectively learns, it verifies, through interviews, how the professor-researcher in the area develops his/her work. This will help not only understand his/her attitudes both as professor and as researcher, but also establish a differentiated formation proposal for the area based on the combination of teaching and research. Finally, it presents the authors final thoughts and her next steps in the area.